Ursolic-Acid-Enriched Herba Cynomorii Extract Protects against Oxidant Injury in H9c2 Cells and Rat Myocardium by Increasing Mitochondrial ATP Generation Capacity and Enhancing Cellular Glutathione Redox Cycling, Possibly through Mitochondrial Uncoupling. (9th April 2013) - Chen, Jihang; Ko, Kam Ming
Abstract : Mitochondrial decay is considered to be a major contributor to aging-related diseases, including neurodegenerative diseases, cardiovascular disorders, and certain metabolic diseases. Therefore, the maintenance of mitochondrial functional capacity and antioxidant status should play an essential role in preventive health. Herba Cynomorii, which is one of the most potent "Yang-invigorating" Chinese tonic herbs, was found to increase mitochondrial ATP generation capacity (ATP-GC) in rat hearts ex vivo . In the present study, we demonstrated that HCY2, an active fraction of Herba Cynomorii, and its major ingredient ursolic acid (UA) could protect against hypoxia/reoxygenation-induced cell apoptosis in H9c2 cells in vitro and also against ischemia/reperfusion-induced injury in rat hearts ex vivo . The cardioprotection was associated with an increase in ATP-GC and an enhancement of glutathione redox cycling. The results suggest that UA may be one of the active ingredients responsible for the cardioprotection afforded by Herba Cynomorii, and this effect may be mediated, at least in part, by enhancement of mitochondrial functional capacity and antioxidant status, possibly through the induction of mitochondrial uncoupling.